1973
DOI: 10.1090/s0002-9947-1973-0326728-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sections of symplectic Stiefel manifolds

Abstract: The cross-section problem for the symplectic Stiefel manifolds is solved, using the now-proved Adams conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…In the papers [3,5,12,18,19,23] the problem of when the structure group G n in one of the fibrations (1.1)-(1.3) can be reduced to a group G = SU(k) or Sp(k) via a standard inclusion G → G n was solved and the results were expressed in terms of complex and quaternionic James numbers in a way similar to the result quoted above. The following theorem can be regarded as a generalization of these results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the papers [3,5,12,18,19,23] the problem of when the structure group G n in one of the fibrations (1.1)-(1.3) can be reduced to a group G = SU(k) or Sp(k) via a standard inclusion G → G n was solved and the results were expressed in terms of complex and quaternionic James numbers in a way similar to the result quoted above. The following theorem can be regarded as a generalization of these results.…”
Section: Resultsmentioning
confidence: 99%
“…Classical computations in [1,3,5,23] showed that t(r) = a(r), b(r) and c(r) in the real, complex and quaternionic cases, respectively. Classical computations in [1,3,5,23] showed that t(r) = a(r), b(r) and c(r) in the real, complex and quaternionic cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Let c F k be the F-James number computed by Adams [1] for F = R, by Adams and Walker [2] for F = C, and by Sigrist and Suter [13] for F = H. The key result of this paper is the following desuspension lemma which was unnoticed by Namboodiri [9] and Önder [11].…”
Section: Lemma 4 If ρ Has a G-section Then S(m) G S(m ⊗ F ξ K−1 ) Tmentioning
confidence: 90%
“…Let F be one of the classical division algebras over R, namely, the real numbers R, the complex numbers C, or the quaternionic numbers H. Let G be a compact Lie group, M be a finite-dimensional right F-representation space of G with a G-equivariant F-inner [1] in 1962 for the real case, by Adams and Walker [2] in 1965 for the complex case, and by Sigrist and Suter [13] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation